Review of Historical Background and the Role of the Mosque in Social and Religious Context: A Case Study of Masjid Nurul Ikhsan in Central Bengkulu - Monalisa, Agnes; Nindri, Meike Pusita Yulia; Lestari, Anita Fuji; Cahyadi, Ashadi (Jurnal Kajian Manajemen Dakwah, 2024)
This study explores the role and contribution of Masjid Nurul Ikhsan in the social and religious context of its surrounding community. The aim is to understand the history and role of the mosque through a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis. The study reveals that the mosque plays a crucial role as a center of worship, education, and social activities. The implication is that the mosque needs to adapt and continue developing innovative programs to support the welfare of the community.